Sodium arsenite-induced changes in the wood of esca-diseased grapevine at cytological and metabolomic levels - Trouvelot, Sophie; Lemaitre-Guillier, Christelle; Vallet, Julie; Jacquens, Lucile; Douillet, Antonin; Harir, Mourad; Larignon, Philippe; Roullier-Gall, Chloé; Schmitt-Kopplin, Philippe; Adrian, Marielle; Fontaine, Florence (Frontiers in Plant Science, 2023)
In the past, most of the grapevine trunk diseases (GTDs) have been controlled by the treatments with sodium arsenite. For obvious reasons, it was banned in the vineyards and consequently, the management of GTDs is difficult due to the lack of methods with similar effectiveness. Sodium arsenite is known to have a fungicide effect and to affect the leaf physiology but its effect on the woody tissues where the GTD pathogens are present is still poorly understood. This study thus focuses on the effect of sodium arsenite in woody tissues, particularly in the interaction area between asymptomatic wood and necrotic wood resulting from the GTD pathogens activities. The main results are that sodium arsenite impacts both metabolome and structural barriers in the plant wood. We reported a stimulator effect on plant secondary metabolites in the wood, which add to its fungicide effect. Moreover, the pattern of some phytotoxins is affected, suggesting the possible effect of sodium arsenite in the pathogen metabolism and/or plant detoxification process. This study brings new elements in the understanding of the mode of actions of sodium arsenite, useful to develop sustainable and eco-friendly strategies to better manage GTDs.